Evaluation of Cardiovascular Risk among Carpenter Cabinetmakers in the Dakar Region: Study of Vascular Function and Heart Rate Variability (International Journal of Physiology, 2024)
Background: Contemporary concerns recognize atmospheric air pollution as a significant contributor tocardiovascular diseases. Notably, wood dust, colloquially known as sawdust, emerges as a source of air pollution.Our investigation sought to assess the impact of wood dust on the cardiovascular health of carpenters in the Dakarregion.Methods: This cross-sectional study encompassed one hundred (100) carpenters in the Dakar region. Acomprehensive questionnaire gathered data on socio-demographic features, professional experience, medicalhistory, preventive measures, and lifestyle habits. Vascular function assessment involved determining finger-toepulse wave velocity (ft-PWV) using a popmeter. Additionally, we screened for obliterative arteriopathy of thelower limbs (OALL). Heart rate variability measurement provided insights into the sympatho-vagal balanceof nervous control over cardiac activity.Results: The average age in our population was 38 ±7.2 years, with a body mass index of 22.7 ±2.8 kg/m2. A majority(69%) worked an average of 10.2 hours per day for six days per week. Approximately 73% of the shops were observedto be enclosed. Respiratory and ocular symptoms were prevalent among participants. Analysis using the Pop meterrevealed arterial stiffness (ft-PWV>10 m/s) in 3% of participants, and 11% exhibited arterial hypertension.OALL was present in 8% of participants. Furthermore, a positive correlation (P=0.003; r=0.581) between ft-PWVVand mean arterial pressure was noted. Data on cardiac variability indicated a substantial proportion of participantsdisplaying decreased tone in the cardiac-parasympathetic nervous system in the supine position (94.73% hadRMSSD values above norms). Notably, abnormal activation of the parasympathetic system (HF) and decreasedsympathetic system activity (low values for HF, LF, and LF/HF compared with norms) were observed in theorthostatic position.Conclusion: Carpentry work in environments with elevated air pollution, potentially emanating from wooddust, poses inhalation risks for workers. The inhalation of wood dust appears linked to an increased risk andexacerbation of cardiovascular complications.